Penerapan Biofertilizer Dan Teknologi Terpadu Untuk Meningkatkan Hasil Pertanian Organik - * Zahara (CV. SINAR HOWUHOWU, 2025)
Organic farming faces challenges related to productivity and resource efficiency. This study aims to evaluate the effectiveness of biofertilizers and integrated technology in improving the yield and quality of organic crops. The research employed a field experiment using a randomized complete block design (RCBD) with four treatments: control, biofertilizer, integrated technology, and a combination of both. Observed parameters included plant growth, crop yield, organoleptic quality, and soil fertility. Results indicated that the combination of biofertilizers and integrated technology increased productivity by up to 30% compared to the control, improved crop quality, and enhanced water and nutrient use efficiency. The application of both approaches also contributed to environmentally friendly farming practices by reducing chemical fertilizer use and operational waste. These findings confirm that integrating biofertilizers and integrated technology is an effective strategy to support productive, sustainable, and eco-friendly organic farming.